Microendoscopic Decompression for Lumbar Spinal Stenosis Associated with Adjacent Segment Disease following Lumbar Fusion Surgery: 5-year Follow-up of a Retrospective Case Series - Murata, Shizumasa; Minamide, Akihito; Nakagawa, Yukihiro; Iwasaki, Hiroshi; Taneichi, Hiroshi; Schoenfeld, Andrew J.; Simpson, Andrew K.; Yamada, Hiroshi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Study Aims Surgical treatment options for lumbar spinal stenosis (LSS) based on adjacent segment disease (ASD) after spinal fusion typically involve decompression, with or without fusion, of the adjacent segment. The clinical benefits of microendoscopic decompression for LSS based on ASD have not yet been fully elucidated. We aimed to investigate the clinical results of microendoscopic spinal decompression surgery for LSS based on ASD.Patients and Methods From 2011 to 2014, consecutive patients who underwent microendoscopic spinal decompression without fusion for LSS based on ASD were enrolled. Data of 32 patients (17 men and 15 women, with a mean age of 70.5 years) were reviewed. Japanese Orthopaedic Association score and low back pain/leg pain visual analog scale score were utilized to measure neurologic and axial pain outcomes, respectively. Additionally, after the surgeries, we analyzed the magnetic resonance imaging (MRI), computed tomography (CT) scans, or radiographs to identify any new instabilities of the decompressed segments or progression of ASD adjacent to the decompressed segments.Results The Japanese Orthopaedic Association recovery rate at the 5-year postoperative visit was 49.2%. The visual analog scale scores for low back pain and leg pain were significantly improved. The minimum clinically important difference for leg pain (decrease by ≥24 mm) and clinically important difference for low back pain (decrease by ≥38 mm) were achieved in 84% (27/32) and 72% (23/32) of cases, respectively. Regarding new instability after microendoscopic decompression, no cases had apparent spinal instability at the decompression segment and adjacent segment to the decompressed segment.Conclusions Microendoscopic spinal decompression is an effective treatment alternative for patients with LSS caused by ASD. The ability to perform neural decompression while maintaining key stabilizing structures minimizes subsequent clinical instability. The substantial clinical and economic benefits of this approach may make it a favorable alternative to performing concurrent fusion in many patients.
Keywords: lumbar spinal stenosis; microendoscopic decompression; adjacent segment disease